Retrograde Instillation of Methylene Blue in the Difficult Diagnosis of BPF - F. Ravenna; C. Feo; N. Calia; C. Avoscan; C. Barbetta; G. N. Cavallesco (Case Reports in Medicine)
We report two cases in which we were able to diagnose bronchopleural fistula through retrograde methylene blue instillation during bronchoscopy. In the first case, methylene blue was injected through an abdominal drain, followed by air instillation and detected in the left bronchial tree, demonstrating the presence of a fistula in the lingula’s bronchus. In the second case, methylene blue was injected into a pleural drain, through a breach on a surgical suture and detected in the right bronchial tree, demonstrating the presence of a fistula in the right inferior bronchus. The retrograde instillation of methylene blue, through a drain in the abdomen or the thoracic wall, is a safe, cheap, and practical method that allows the bronchoscopist to identify the presence of a fistula and, more importantly, to identify the exact point on the bronchial tree where a fistula is located. This provides the possibility of sealing the fistula with a variety of devices. It is our opinion that this procedure should be considered a primary method of diagnosis when a bronchopleural fistula is suspected and a drain on the thoracic or abdominal wall is positioned such that effusions are able to drain.